A study of creep of rocks - Singh D.P. (My University, 2025)
Knowledge of the time-dependent behaviour of rocks can be of considerable help in understanding many aspects of rock engineering. Hence, it is considered essential that the time-dependent properties of rocks be investigated in the laboratory and field. Facility for studying time-dependent deformation was created at the University of Melbourne. Measures were taken to achieve a constant temperature in the creep testing laboratory and a long-term loading machine consisting of a gas-hydraulic system and a loading frame was designed to apply the sustained pressure on the rock specimens. Axial and lateral deformation of the specimens were measured by the dial gauges. Both the axial and the lateral creep curves of Sicilian marble specimens exhibited the three stages of the idealized creep curve. The creep rate in lateral direction was found far greater than in axial direction. A power curve was found to fit most creep curves of Sicilian marble specimens up to the steady state stage of creep while subjected to stresses beyond their yield strength. The mode of fracture of the specimens in creep tests was similar to the mode observed in the uniaxial compression tests. © 1975.